Improvement of the performance of wearable textile antenna - Loni1, Janabeg; K. Singh, V; Kumar Tripathi, Anand; Soo Chae, Gyoo; Sharma, Ashis; Kumar Bhoi, Akash (International Journal of Engineering and Technology, 2018)
In this article low cost wearable textile receiver antenna with copper ground is proposed. The anticipated antenna has the ability to receive the frequency between 2.185 GHz to 6.625 GHz. The antenna parameters have been improved through the optimization technique. A com-parison is studied and described among some existing and anticipated antenna. The proposed wearable receiver antenna is applicable to re-ceive radio wave energy available in the range 2.185 GHz to 6.625 GHz.Â Â